Regression Analyses for Occlusal Force Based on Tooth Displacement - Furuki, Yuzuru; Nakamura, Noriko; Nozaki, Koske; Shin, Chiharu; Miura, Hiroyuki; Hasegawa, Shigeo; Tanaka, Yoshihiro (The Journal of Japanese Society of Stomatognathic Function, 2007)
The tooth displacement and the occlusal force are simultaneously measured by means of the tooth displacement transducer and Prescale. Based on the result, the method is discussed, by which the physiological occlusal force during clenching at the intercuspal position without anything between the upper and the lower teeth is evaluated from the distance of tooth displacement. The subject is the male at the age of 27 with the normal dentition and occlusion. The displacement of the subject tooth, the upper left first molar, is measured by means of the displacement transducer type M-3. The occlusal force of tooth is measured with the Prescale. At this time, observing the distance of the tooth displacement on the oscilloscope, the subject is instructed to adjust the occlusal force during clenching. The occlusal form and the facets are three dimensionally recorded on the study model by means of the apparatus recognizing occlusal form (Optrace) . After the normal line of every facet, the occlusal vector on every facet is calculated from the magnitude of the measured occlusal force, which leads the occlusal vector of the subject tooth. There is the positive correlation between the tooth displacement and the occlusal force. The coefficient of correlation is 0.847. Therefore, the linear model is applied to evaluate the physiological force from the tooth displacement. As a result, F=2.38D+50.1 (F: force [N], D: tooth displacemet [μm] ) is obtained. With this regressive formula, the evaluated occlusal force is 114.7-125.9 N with the range of 70-160μm tooth displacement in the 95% confidence interval. This study suggests that the physiological force can be evaluated from the tooth displacement.